1987
DOI: 10.1056/nejm198707163170303
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Metabolic Effects of Recombinant Human Insulin-like Growth Factor I in Healthy Adults

Abstract: Insulin-like growth factor I (IGF I) is structurally similar to insulin and shares many of its biologic properties. We compared the short-term metabolic effects of recombinant IGF I (100 micrograms [13.3 nmol] per kilogram of body weight) and insulin (0.15 IU [1 nmol] per kilogram) in eight healthy volunteers (four men and four women). The hypoglycemic responses to both hormones were nearly identical in the doses used. The lowest blood glucose levels were reached after 30 minutes: 1.98 +/- 0.44 mmol per liter … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

14
270
1
2

Year Published

1992
1992
2013
2013

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 546 publications
(287 citation statements)
references
References 21 publications
14
270
1
2
Order By: Relevance
“…The mechanism of the hyperglycemia is not completely understood, but data that link the IGF-I ligand system and glucose metabolism may provide clues to the metabolic effects of anti-IGF-IR therapy. IGF-I administration in humans results in hypoglycemia, decreased serum levels of fatty acids, and increased lipogenesis [81,82]. Recombinant IGF increases insulin sensitivity in the liver and muscle in patients with type II diabetes mellitus and results in better glucose control [83].…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…The mechanism of the hyperglycemia is not completely understood, but data that link the IGF-I ligand system and glucose metabolism may provide clues to the metabolic effects of anti-IGF-IR therapy. IGF-I administration in humans results in hypoglycemia, decreased serum levels of fatty acids, and increased lipogenesis [81,82]. Recombinant IGF increases insulin sensitivity in the liver and muscle in patients with type II diabetes mellitus and results in better glucose control [83].…”
Section: Ongoing Clinical Trialsmentioning
confidence: 99%
“…I GF-I promotes growth and differentiation in a variety of tissues (1). IGF-I also mimics some of the metabolic actions of insulin, including stimulation of glucose and amino acid uptake and inhibition of gluconeogenesis (2)(3)(4). These effects are largely mediated by the IGF-I receptor, although IGF-I can also bind to the insulin receptor with low affinity (5,6).…”
mentioning
confidence: 99%
“…One may speculate that the primary role of liver-derived IGF-I is the regulation of carbohydrate and lipid metabolism, rather than growth promotion. Clinical studies of short-term metabolic effects of recombinant human IGF-I (rhIGF-I) in healthy adults have shown that IGF-I is 6% as potent as insulin on a molar basis in the production of hypoglycemia (2). A patient with severe IGF-I deficiency (secondary to a homozygous deletion of a part of the IGF-I gene) had insulin resistance that was normalized by treatment with rhIGF-I (11).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The IGF-I and IGF-II polypeptides are insulin-like growth factors which have structural homology with insulin [I], Although the major effects of the IGF's are on cell replication and differentiation [I ,2], the IGF's demonstrate effects similar to insulin on glucose metabolism [3,4]. IGF-I exerts a stimulatory effect on glucose transport in rat 141 and human skeletal muscle [S].…”
Section: Introductionmentioning
confidence: 99%